The acoustic and electroglottographic methods of determination the vocal folds vibration fundamental frequency - Wszołek, Wiesław; Kłaczyński, Maciej; Engel, Zbigniew (Archives of Acoustics, 2007)
There are many methods of measuring fundamental frequency of vocal folds’ vibrations.The mentioned function can be estimated in several ways, either through internal measurements(optical methods) or external measurements (the acoustic analysis of the voice, electricmethod). Electric methods (EGG), based on analysis of the electroglottographic signal are oftenapplied. However acoustic methods or registration and processing the speech signals canbe applied. The authors’ research proves that maximum information on phonetic action of larynxcan be assembled by delimitation of the fundamental frequency parameters. Thus the exactdetermination of pitch function makes a priority in the glottal area research. The spectrumcharacter of speech wave is connected with the fundamental frequency ($F_0$) of human vocalfolds vibration. As it is considered, $F_0$ of the source during voicing contains an abundance ofinformation on the larynx pathology, individual trait, the emotional state and ethnographicalorigin of speaker. The literature demonstrates only limited research that conducted simultaneousmeasurement of fundamental frequency by the EGG and with the acoustics methods. Thepresent paper presents results of such research, including simultaneous processing EGG andacoustic data. The analysis of the $F_0$ function exactitude and the usefulness of these methodswere executed too.